Penerapan Prinsip Syariah Pada Akad Musyarakah Mutanaqishah Di Bank Syariah Dalam Bentuk Akta Notaris Yang Mengandung Klausula Eksonerasi - Mohamad Hilal Nu'man (Bayani, 2021)
The clauses contained in the sharia financing contract deed are clauses that have become the standard form in making the sharia financing contract deed. In making contracts in Islamic banking, in general, a standard format applies where a draft has been prepared by the bank. Almost all contracts, including muasyarakah mutanaqishah financing contracts, then the format or draft becomes the basis for making a musyarakah mutanaqishah financing contract deed made by a notary, for this reason it is necessary to study and analyze the standard clauses in the muasyarakah mutanaqishah financing contract which is made in the form of an authentic deed associated with the principle sharia, especially in the clause on Guarantees, Defaults and Consequences of Defaults. This study uses a normative juridical approach by examining literature or secondary data, is a descriptive legal research analysis in order to find data carefully and completely about the characteristics of a situation or symptoms that can help find the Exoneration Clause in the Musyarakah Mutanaqishah Contract at the Bank. Sharia in the Form of a Notary Deed Linked to Sharia Principles. In this study, it was found that the contract made did not show conformity with sharia principles in the musyarakah mutanaqishah financing contract which was made in the form of an authentic deed. Musyarakah mutanaqishah financing contracts in Islamic banking are linked to sharia principles which are made in the form of an authentic deed manifested in the form of an agreement and the things that are agreed upon are based on an agreement, in a contract ratified by a notary that must be achieved freely without coercion by inserting a clause into the contract. made in accordance with the interests of the parties as long as it does not result in falsehood.